New technologies to detect electron beam signals - Alizoti, Alion (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Electricity and electronic devices are playing an overwhelming role in human society. As physical studies are extending the applications of electric currents in metals, electrolyte liquids, gases, vacuum, semiconductors, or superconductors, this paper focuses on the electronic current beam in the vacuum. To this aim, experiments with cathode ray tubes and cathode ray balloons are conducted in our physics lab classes. Therefore, important observations and measurements are accomplished, concerning several physical qualities and quantities. As the electron beam is being visibly observed, electric signals are detected from the beamed target. The observed qualities are assembled and listed, whilst data from the measured quantities are displayed using table and graph plotting.